What Makes Domestic Tourists Satisfied with Shopping in Bali? The Influence of Place Attachment, Shopping Motivation, and Shopping Experience - Putu Gde Arie Yudhistira; Jellycha Mutiara Kurnia Putri; Eka Nova Irwani (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
Shopping for souvenirs is often considered an essential part of the travel experience for many tourists. This study examines the relationship between place attachment and shopping motivation as independent variables, shopping satisfaction as a dependent variable, and shopping experience as a mediator. The findings indicate that place attachment may influence shopping pleasure indirectly, through the mediating role of shopping experience. In contrast, shopping satisfaction is affected by shopping motivation both directly and indirectly. A sample size of 308 respondents who had participated in tourism shopping at Sukawati Art Market, Gianyar, Bali, was used to validate the proposed model. The validation was conducted using PLS-SEM through outer and inner models with SmartPLS 4, using a 1-tailed test. The study employed a quantitative approach and collected data through a survey questionnaire. The results of this research hold theoretical and practical implications for increasing the understanding of shopping satisfaction of domestic tourists.